A spatiotemporal analysis of transit accessibility to low-wage jobs in Miami-Dade County. (January 2022) - Yan, Xiang; Bejleri, Ilir; Zhai, Liang
Abstract: An essential function of public transit is to connect low-wage earners to their jobs or potential employment opportunities. Previous research has shed light on this issue by examining how transit accessibility varies across space, the temporal variations of transit accessibility, and the modal disparity between public transit and automobiles, but often in a disjointed manner. This study contributes to the literature by considering all these issues together in a unified analytical framework. Specifically, we conduct a spatiotemporal analysis of transit accessibility to low-wage jobs and of the disparities between transit accessibility and auto accessibility. Our analysis focuses on Miami-Dade County in Florida, a region defined by a low-density, auto-oriented urban form and a Hispanic-majority population. We find that residents of low-income and Black-majority neighborhoods enjoy a higher level of transit accessibility because of their concentration in high-density urban areas. Often located in suburban and rural locations, Hispanic-majority neighborhoods have a much lower level of accessibility. Not surprisingly, transit accessibility is higher in peak hours than other hours of the day. The gap between transit accessibility and auto accessibility is striking, with car users being able to access eight times more low-wage jobs than transit riders on average. The accessibility gap is smaller during peak hours and in the downtown Miami area; but still, auto accessibility is about three times that of transit accessibility. The large disparities between transit accessibility and auto accessibility provide a strong rationale for additional funding support to promote transit services, such as on-demand microtransit services, in lower-density areas and during off-peak hours.